(untitled) (LEARNing Landscapes, 2012)
In this paper, the authors discuss creativity and the impact it might have on teaching and learning. The authors believe that imaginative play, at all ages, helps all people (children especially) create healthy environments and spaces that expand their learning. The authors contend that teaching for imagination—which asks little more than creating and trusting an ecological space that engenders it—seldom is considered a priority. Given the emphasis on creativity in the real world and the virtual digital world, the authors believe it is important to add to the body of knowledge through continued research in this field.